Malignancies in adult patients with common variable immunodeficiency - Eunice Giselle López-Rocha; Karen Alicia Rodríguez-Mireles; Nora Hilda Segura-Méndez; Marco Antonio Yamazaki-Nakashimada (Revista Alergia México, 2015)
Background: Common variable immunodeficiency (CVID) implies an increased risk of cancer, with an estimated incidence of 11-13%, particularly during the 5th and 6th decade of life. B cell-Hodgkin lymphomas are the more frequent cancer, followed by non-Hodgkin lymphoma and epithelial tumors (gastric, breast, bladder and cervix).